Ultimate load of composite floors in fire with flexible supporting edge beams - Nguyen, Tuan Trung (2016)
A number of previous analytical studies have been conducted to predict the enhanced load-bearing capacity of a concrete slab due to tensile membrane action. These analytical approaches are based on an implicit assumption that the vertical supports along the slab panel boundaries during a fire do not deform. In reality, the edge beams do deflect even though they are fire-protected, and this assumption may not be valid. This may render any approaches based on this assumption to be unconservative when there is significant deflection of protected edge beams. This work looks at the actual boundary condition where the protected edge beams do deflect, and the slab still bends in synclastic curvature. The authors propose a semi-analytical model which can predict the load-bearing capacity of composite beam–slab floor systems enhanced by tensile membrane action under fire conditions, but weakened by deflection of protected edge beams. The novelty is that the slab enhancement factor actually takes account of the deflections of protected edge beams. The new model can consider the beam–slab interaction under fire conditions and give information of the edge beams. Validations with the test results show that the new model gives fairly accurate and conservative predictions of the load-bearing capacity of composite beam–slab systems.